Effects of a multi-strain probiotic supplement for 12 weeks in circulating endotoxin levels and cardiometabolic profiles of medication naïve T2DM patients: a randomized clinical trial - Sabico, Shaun (J Transl Med, 2017)
BACKGROUND: The present randomized clinical trial characterized the beneficial effects of a multi-strain probiotics supplementation on improving circulating endotoxin levels (primary endpoint) and other cardiometabolic biomarkers (secondary endpoint) in patients with T2DM. METHODS: A total of 78 adult Saudi T2DM patients (naïve and without co-morbidities) participated in this clinical trial and were randomized to receive twice daily placebo or probiotics [(2.5 × 10(9) cfu/g) containing the following bacterial strains: Bifidobacterium bifidum W23, Bifidobacterium lactis W52, Lactobacillus acidophilus W37, Lactobacillus brevis W63, Lactobacillus casei W56, Lactobacillus salivarius W24, Lactococcus lactis W19 and Lactococcus lactis W58 (Ecologic(®)Barrier)] in a double-blind manner for 12 weeks. Anthropometrics and cardiometabolic profiles were obtained at baseline and after 12/13 weeks of treatment. RESULTS: After 12/13 weeks of intervention and using intention-to-treat analysis, no difference was noted in endotoxin levels between groups [Placebo − 9.5% vs. Probiotics − 52.2%; (CI − 0.05 to 0.36; p = 0.15)]. Compared with the placebo group however, participants in the probiotics groups had a significant but modest improvement in WHR [Placebo 0.0% vs. Probiotics 1.11%; (CI − 0.12 to − 0.01; p = 0.02)] as well as a clinically significant improvement in HOMA-IR [Placebo − 12.2% vs. Probiotics − 60.4%; (CI − 0.34 to − 0.01; p = 0.04)]. CONCLUSION: Using a multi-strain probiotic supplement daily for 12/13 weeks significantly improved HOMA-IR and modestly reduced abdominal adiposity among medication naïve T2DM patients. Trial Registration: ClinicalTrials.gov Identifier: NCT01765517, Registered January 10, 2013 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12967-017-1354-x) contains supplementary material, which is available to authorized users.